MENGUNGKAP FORMULA KINERJA SDM MELALUI INTERAKSI KOMPENSASI FINANSIAL, PELATIHAN, DAN KNOWLEDGE SHARING - Aan Abdul Azis; Rini Handayani (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
An organization is established based on a program designed with the intention of achieving predetermined goals, so that a quality HR role is needed. Organizations in improving HR require elements, namely guaranteed financial compensation, regular training, knowledge sharing that supports the formation of employee performance quality. A population of 50 employees of PT. Amartha Mikro Fintek was used as a sample of around 50 respondents. Questionnaires were used to collect data. Multiple regression analysis was employed. Training, financial compensation, and knowledge sharing all have a substantial impact on employee performance, according to the results gathered from these factors.